Respuesta :
Answer:
[tex](f+g)(x) = 4x - 2[/tex]
Step-by-step explanation:
f(x) = 7x - 4
g(x) = -3x + 2
To find (f+g)(x) add g(x) to f(x)
That's
[tex](f+g)(x) = 7x - 4 + (- 3x + 2) \\ = 7x - 4 - 3x + 2 \\ = 7x - 3x - 4 + 2[/tex]
We have the final answer as
[tex](f+g)(x) = 4x - 2[/tex]
Hope this helps you
Answer:
[tex]\Large \boxed{(f + g)(x) = 4x - 2}[/tex]
Step-by-step explanation:
We have two functions.
f(x) = 7x - 4
g(x) = -3x + 2
To find (f+g)(x), we have to find the sum of f(x) and g(x).
(f+g)(x) = f(x) + g(x)
(f + g)(x) = 7x - 4 + -3x + 2
Combining like terms.
(f+g)(x) = 7x - 3x - 4 + 2
(f + g)(x) = 4x - 2